(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Large job prospects are created by MSMEs at a cost that is far lower than that of large-scale industries. It also promotes the industrialisation of rural and underdeveloped areas and ensures a wealth and income distribution that is more fairly distributed across the country. The main barrier to the current sector, however, is the lack of strong institutional support because this industry is always faced with numerous difficulties. Therefore, the government needs a specialised financial institution to "fund the unfunded" and promote entrepreneurship and self-employment in the country while also increasing institutional finance to the sector